2008
DOI: 10.1007/s00384-008-0485-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic findings on defecography according to reconstruction method and defecatory disorder following sphincter-saving surgery for rectal cancer

Abstract: Defecography is useful for visualizing and characterizing defecatory disorders following rectal resection. Based on defecography, J-pouch reconstruction offers advantageous volume, while side-to-end anastomosis provides a more acute anorectal angle for patients who have received rectal resection with low anastomosis. A new reconstruction method offering both advantages was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this retrospective study, defecography served as a tool to assess the patient anal sphincter function during different activities, including at rest, squeeze, pushing, and after evacuation, which was helpful for visualizing and characterizing defecatory disorders. It was also found to be useful to diagnose whether there was an anastomotic fistula that was not easy to be detected by colonoscopy, 21,22 although in this study cohort, no anastomotic fistula was found. This is a good tool to judge whether the patient had any contraindications to stoma closure.…”
Section: Discussionmentioning
confidence: 80%
“…In this retrospective study, defecography served as a tool to assess the patient anal sphincter function during different activities, including at rest, squeeze, pushing, and after evacuation, which was helpful for visualizing and characterizing defecatory disorders. It was also found to be useful to diagnose whether there was an anastomotic fistula that was not easy to be detected by colonoscopy, 21,22 although in this study cohort, no anastomotic fistula was found. This is a good tool to judge whether the patient had any contraindications to stoma closure.…”
Section: Discussionmentioning
confidence: 80%
“…There are several examinations that can be performed for anorectal function, such as the clinical score, manometry, defecography, and electromyography. 6,[21][22][23] However, it is difficult to conclude whether these examinations provide accurate results. Defecation is the sum of the functions of all mechanisms of anorectal evacuation.…”
Section: Discussionmentioning
confidence: 99%
“…Thickness of posterior rectal mesenterium (sacral 4 plane in transverse view) was measured by CT or MRI before and after surgery. In addition, the combined anorectal manometry and rectal magnetic resonance imaging (MRI) defecography [ 24 ] were used to evaluate the anorectal pressure and morphological structure of some patients, and to comprehensively evaluate the physiological function and morphological characteristics of anorectal after surgery.…”
Section: Methodsmentioning
confidence: 99%